The devil and the dairy princess : stories - Ponce, Pedro, 1972- (Blue light books., 2021)
Perfect for any reader who enjoys literary realism or speculative fiction, The Devil and the Dairy Princess reveals the episodic history of humanity's romance with narrative, from first love to break-up to hopeful reconciliation.